Racial/Ethnic Differences in Perineal Lacerations in a Diverse Urban Healthcare System. Issue 1 (January 2019) - Williams, Amanda; Gonzalez, Beverly; Fitzgerald, Colleen; Brincat, Cynthia
Abstract : Objectives: The aim of the study was o determine whether variations exist between races/ethnicities in perineal laceration at first vaginal delivery. Methods: We assessed first vaginal deliveries greater than 35 weeks gestation, for a four-year period, in our diverse urban healthcare system. Predictor variable was race/ethnicity with outcome variable of none, first-, second-, third-, or fourth-degree perineal laceration. Race and ethnicity were self-reported and combined into one variable to facilitate analysis. We also collected data on other known risk factors for laceration to adjust our analysis accordingly. Results: A total of 1179 charts met criteria. When comparing none, first-, or second-degree lacerations versus third or fourth degrees (obstetric anal sphincter injuries) race was not a significant factor. We also compared lacerations among the following three groups: none or first degree versus second degree versus obstetric anal sphincter injuries. In this case, Asian and white women were associated with an increasing trend of perineal lacerations as degree of severity increased ( P < 0.0001), whereas black and Latina women were associated with a decreasing trend as severity increased ( P < 0.0001). After adjusting for other significant variables, race was still significant ( P = 0.02). Conclusions: With an urban diverse population, our study demonstrates an association between race/ethnicity and perineal lacerations. As degree of laceration increased, Asian and white women were noted to have more lacerations, and black and Latina women were noted to have fewer. Because perineal lacerations pose a significant risk to future pelvic floor health, the associated factors identified in this study may prove useful in counseling patients on future risk or in identifying the actual risk in underrepresented populations. Abstract : Significant differences in perineal laceration rates by race are noted in a diverse urban healthcare system, even when controlling for known risks of perineal lacerations.